Dissection of a natural RNA silencing process in the Drosophila melanogaster germ line. - Aravin, A.A.; Klenov, M.S.; Vagin, V.V.; Bantignies, F.; Cavalli, G.; Gvozdev, V.A. (Molecular and Cellular Biology, 2004)
To date, few natural cases of RNA-silencing-mediated regulation have been described. Here, we analyzed repression of testis-expressed Stellate genes by the homologous Suppressors of Stellate [Su(Ste)] repeats that produce sense and antisense short RNAs. The Stellate promoter is dispensable for suppression, but local disturbance of complementarity between the Stellate transcript and the Su(Ste) repeats impairs silencing. Using in situ RNA hybridization, we found temporal control of the expression and spatial distribution of sense and antisense Stellate and Su(Ste) transcripts in germinal cells. Antisense Su(Ste) transcripts accumulate in the nuclei of early spermatocytes before the appearance of sense transcripts. The sense and antisense transcripts are colocalized in the nuclei of mature spermatocytes, placing the initial step of silencing in the nucleus and suggesting formation of double-stranded RNA. Mutations in the aubergine and spindle-E genes, members of the Argonaute and RNA helicase gene families, respectively, impair silencing by eliminating the short Su(Ste) RNA, but have no effect on microRNA production. Thus, different small RNA-containing complexes operate in the male germ line.